Observation of WZ production - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We report the first observation of the associated production of a W boson and a Z boson. This result is based on 1.1fb-1 of integrated luminosity from pp̄ collisions at s=1.96TeV collected with the CDF II detector at the Fermilab Tevatron. We observe 16 WZ candidates passing our event selection with an expected background of 2.7±0.4 events. A fit to the missing transverse energy distribution indicates an excess of events compared to the background expectation corresponding to a significance equivalent to 6 standard deviations. The measured cross section is σ(pp̄→WZ)=5.0-1.6+1.8pb, consistent with the standard model expectation. © 2007 The American Physical Society.